2011
DOI: 10.1007/s10464-011-9462-x
|View full text |Cite|
|
Sign up to set email alerts
|

The Cultural Influences on Help‐seeking Among a National Sample of Victimized Latino Women

Abstract: The current study examined the influence of legal status and cultural variables (i.e., acculturation, gender role ideology and religious coping) on the formal and informal help-seeking efforts of Latino women who experienced interpersonal victimization. The sample was drawn from the Sexual Assault Among Latinas (SALAS) Study that surveyed 2,000 self-identified adult Latino women. The random digit dial methodology employed in high-density Latino neighborhoods resulted in a cooperation rate of 53.7%. Women who e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 53 publications
1
45
1
2
Order By: Relevance
“…Using a short version of only instrumental items in a thirteen nation study with 6,543 participants, mean age 38.5 years old, Arrindell, van Well, Kolk, Barelds, Oei et al [22] demonstrated internal consistency (Cronbach α = .83 averaged across the thirteen countries) and a strong correlation (r = .57, p < 0.05) with the Masculine Gender Role Stress (MGRS) scale. Research using both Spanish and English versions of the BSRI among middle aged women (mean age 44 years) has demonstrated reliability of the masculine (α = .78 in English and .76 in Spanish) and feminine (α = .88 in English and .86 in Spanish) scales [23]. Although the Bem Sex Role Inventory has some history of reliability and validity in Brazil [24–26], to the best of our knowledge neither the full nor the 12 item BSRI has been evaluated among older Brazilians.…”
Section: Introductionmentioning
confidence: 99%
“…Using a short version of only instrumental items in a thirteen nation study with 6,543 participants, mean age 38.5 years old, Arrindell, van Well, Kolk, Barelds, Oei et al [22] demonstrated internal consistency (Cronbach α = .83 averaged across the thirteen countries) and a strong correlation (r = .57, p < 0.05) with the Masculine Gender Role Stress (MGRS) scale. Research using both Spanish and English versions of the BSRI among middle aged women (mean age 44 years) has demonstrated reliability of the masculine (α = .78 in English and .76 in Spanish) and feminine (α = .88 in English and .86 in Spanish) scales [23]. Although the Bem Sex Role Inventory has some history of reliability and validity in Brazil [24–26], to the best of our knowledge neither the full nor the 12 item BSRI has been evaluated among older Brazilians.…”
Section: Introductionmentioning
confidence: 99%
“…Data on alcohol-involved college acquaintance rape rates rarely include racial differences, let alone AAs. Although most victims eventually tell someone about a rape (Sabina, Cuevas, & Schally, 2012), AAs have not been examined with regard to their disclosure behavior.…”
mentioning
confidence: 99%
“…Reporting of forced-sex experiences involves multiple complex factors and minority women may experience additional stressors associated with race and/or ethnicity (Olive, 2012). For Hispanic women, issues involving acculturation, economic resources, immigrant status, language barriers, and access to community resources (Cuevas, Sabina, & Bell, 2012; Sabina, Cuevas, & Schally, 2012) may contribute to underreporting. African American women may also underreport forced sex because of beliefs in sexual stereotypes and rape myths, self-blame, stigma, a cultural mandate to protect an African American male perpetrator as well as a lack of health insurance (Bryant-Davis, Chung, & Tillman, 2009; Long, Ullman, Starzynski, Long, & Mason, 2007; Tillman, Bryant-Davis, Smith, & Marks, 2010).…”
Section: Discussionmentioning
confidence: 99%